Tuberculosis diagnosis in the aged: barriers to accessing health services - Oliveira, Annelissa Andrade Virgínio de; Sá, Lenilde Duarte de; Nogueira, Jordana de Almeida; Andrade, Séfora Luana Evangelista de; Palha, Pedro Fredemir; Villa, Tereza Cristina Scatena (Revista da Escola de Enfermagem da USP, 2013)
This study was performed with the objective to analyze the barriers to diagnosing tuberculosis in the aged and access to health services in the city of João Pessoa, Paraíba, Brazil. This qualitative study included the participation of seven aged women with tuberculosis. Interviews were used for data collection. The empirical material was organized using Atlas.ti 6.0, and analyzed according to the techniques of discourse analysis. The identified barriers related to the access to health services to confirm the diagnosis were: the operating hours of family health units; transferred responsibilities; home visits without controlling communicants; delay of the health service in suspecting the disease and the patient's repeated visits to the health center before being informed about the diagnosis. Despite the identification of common barriers that tuberculosis patients of all ages must deal with, because of the vulnerability of the elderly, health services should implement control actions so as to prevent the disease becoming a common condition in this population.